PENCEMARAN LINGKUNGAN MENURUT UNDANG-UNDANG NO.32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (PPLH) - ALINE FEBRIANY LOILEWENDAN; TITIN TITAWATI; GEDE TUSAN ARDIKA; RAMLI RAMLI (GANEC SWARA, 2022)
This study aims to examine and analyze what sanctions are given to perpetrators of pollution and environmental destroyers, and what factors hinder the law enforcement process in Indonesia. This study uses a form of normative legal research, namely research based on written legislation and various literatures related to the problems that will be discussed in this study. Sources of legal research can be divided into research sources in the form of primary legal materials consisting of legislation, official records or minutes in making legislation and judges' decisions, while secondary materials in the form of all publications on law which is not official documentation, publications on law include textbooks, legal dictionaries, legal journals and commentaries on law. Sanctions given to perpetrators of pollution and environmental destruction consist of administrative aspects, civil aspects, and criminal aspects. The factors that hinder the law enforcement process in Indonesia are; Legal Facilities, Law Enforcement Officials, Facilities and Facilities, Licensing, Environmental Impact Analysis System (AMDAL), Community Legal Awareness of the Proper Environment and compliance with legal provisions.